Ethnopharmacology, phytochemistry, pharmacology, clinical applications and toxicology of the genus Stellera Linn.: A review. (10th January 2021) - Zhang, Nuan; He, Jun; Xia, Cong-Yuan; Lian, Wen-Wen; Yan, Yu; Ding, Kang; Zhang, Ya-Yao; Xu, Jie-Kun; Zhang, Wei-Ku
Abstract: Ethnopharmacological relevance: The genus Stellera Linn. consists of species of perennial herbs and shrubs, and is mainly distributed in the temperate regions of east Asia to west Asia. There are 10∼12 species in the world, two species in China: Stellera chamaejasme Linn. and Stellera formosana Hayata ex Li. As recorded, the roots of Stellera species are used to dissipate phlegm and relieve pain. The roots and the barks can be used for papermaking. Aim of this review: This review aims to summarize the ethnopharmacological uses, chemical constituents, pharmacological activities, clinical applications and toxicology of the genus Stellera to better understand their therapeutic potential in the future. Materials and methods: The relevant information of the genus Stellera was collected from scientific databases (Pubmed, ACS website, SciFinder Scholar, Elsevier, Google Scholar, Web of Science and CNKI). Information was also gathered from 'Flora Republicae Popularis Sinicae (〈〈中国植物志〉〉)', folk records, conference papers on ethnopharmacology, Ph.D. and Masters′ Dissertation. Results: Stellera plants have been studied as traditional folk medicines all around the world. The chemical constituents of Stellera species mainly comprise terpenoids, flavonoids, coumarins, lignans, and so on. Extracts and compounds of Stellera species exhibit extensive pharmacological activities, such as anti-tumor, anti-viral, anti-convulsive, anti-epileptic, anti-bacterial and anti-insect activities, etc . Clinical applications have suggested that the genus Stellera has the effects in treating several skin diseases and cancers, however, the results should be further verification. The genus Stellera plants are toxic and should be used reasonable. Conclusion: This paper reviewed the ethnopharmacological uses, chemical constituents, pharmacology, clinical applications and toxicology of the genus Stellera . The genus Stellera has broad application prospects. However, further in-depth studies are needed to determine the medical uses of the genus and its chemical constituents, pharmacological activities, clinical applications and toxicology. Graphical abstract: Image 1